Lactobacillus plantarum LP104 ameliorates hyperlipidemia induced by AMPK pathways in C57BL/6N mice fed high-fat diet - Yue Teng; Yu Wang; Yuan Tian; Yi-ying Chen; Wu-yang Guan; Chun-hong Piao; Yu-hua Wang (Journal of Functional Foods, 2020)
Lactobacillus plantarum LP104 was isolated with excellent antioxidant properties from kimchi. In order to evaluate the role of LP104 in improving hyperlipidemia in high-fat-diet mice, C57BL/6N mice were randomly assigned into three groups treated with different diets: normal chow (Control), HFD, and HFD with L. plantarum LP104. After eight weeks, L. plantarum LP104 treatment significantly reduced HFD-induced body weight gain and the levels of serum or liver TC, TG, LDL, ALT, AST, LPS and TNF-α, and elevated liver HDL levels. The liver lipid accumulation was decreased in L. plantarum LP104 group. L. plantarum LP104 could activate the AMPK/Nrf2/CYP2E1 related pathway and regulate expressions of related proteins by using western blotting. Therefore, L. plantarum LP104 will improve hyperlipidemia, liver metabolic disorders, and liver oxidative stress response.